Designing an open-source application to record library gate counts in response to COVID-19. Issue 1 (2nd January 2022) - Perera, Damith; Nykolaiszyn, Juliana M.
Abstract: In response to the COVID-19 pandemic, the Oklahoma State University Library developed an open-source application to record real-time building capacity. Library student security tracks building entrances and exits via the program, with current visitor numbers appearing on the library's website via an API. This effort helps administrators have a clear picture of building capacity during opening hours for data-driven decision-making and provides users information regarding the library's level of activity.